Causal analysis procedure focused on small software development organizations - Zúñiga-Silva, Kelly Yohanna; Ardila-Albarracín, Carlos Alberto; Pino-Correa, Francisco José (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Very Small Entities (VSE) dedicated to software development lack of enough resources to adopt causal analysis practices, defined in models as CMMI, due to their complexity and costs. It is important to detect the generated defects in the development process, and to make a systematic analysis aimed at determining its causes. However, identifying those root causes is an arduous task, and failing to do so leads to wrong decisions that either fail to solve the problem or even make it worse. On this basis, this paper proposes a causal analysis procedure focused on small organizations PAC-DS (according to its initials in Spanish), which includes activities aimed at identifying the defects causes. After its evaluation in a preliminary case study, the utility of the procedure was evidenced.